An anti-virulence drug targeting the evolvability protein Mfd protects against infections with antimicrobial resistant ESKAPE pathogens - Seav-Ly Tran; Lucie Lebreuilly; Delphine Cormontagne; Samantha Samson; Thu Ba Tô; Marie Stosskopf; Rozenn Dervyn; Anne Grießhammer; Jacobo de la Cuesta-Zuluaga; Lisa Maier; Thierry Naas; Simona Mura; et al. (Nature Communications)
Abstract The increasing incidence of antibiotic resistance and the decline in the discovery of novel antibiotics have resulted in a global health crisis, particularly, for the treatment of infections caused by Gram-negative bacteria, for which therapeutic dead-ends are alarming. Here, we identify and characterize a molecule, NM102, that displays antimicrobial activity exclusively in the context of infection. NM102 inhibits the activity of the non-essential Mutation Frequency Decline (Mfd) protein by competing with ATP binding to its active site. Inhibition of Mfd by NM102 sensitizes pathogenic bacteria to the host immune response and blocks infections caused by the clinically-relevant bacteria Klebsiella pneumoniae and Pseudomonas aeruginosa, without inducing host toxicity. Finally, NM102 inhibits the mutation and evolvability function of Mfd, thus reducing the bacterial capacity to develop antimicrobial resistance. These data provide a potential roadmap for the development of drugs to combat antimicrobial resistance.